POTENSI PENGEMBANGAN USAHATANI KENIKIR DI KOTA KENDARI - Minggu Lestari Ningsih; Ilma Sarimustaqiyma Rianse; Nini Mila Rahni; Sri Rejeki; Muhammad Iqbal Kusumabaka Rianse; RH. Fitri Faradilla; Tamrin Tamrin; Hadi Sudarmo; Mariani L Mariani (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
This study aims to evaluate the potential for developing kenikir cultivation in Kendari City through a financial feasibility approach to kenikir cultivation by comparing two treatments, namely the use of bokashi fertilizer and no fertilizer use. The method used is a quantitative descriptive approach, with primary data collected through direct observation of production cost components and crop yields. The analysis was carried out by calculating the total production costs, income, and R/C ratio as indicators of business efficiency. The results show that kenikir cultivation without fertilizer produces an R/C ratio of 1.24 with total costs of IDR 12, 128,000 and income of IDR 15,060,000, while the use of bokashi fertilizer resulted in an R/C ratio of 1.44 with total costs of IDR 19,128,000 and income of IDR 27,480,000. These results show that both treatments are financially feasible (R/C>1), but the treatment with bokashi fertilizer is more efficient and profitable. The conclusion of this study is that kenikir cultivation using bokashi fertilizer is more financially efficient and feasible to develop, and has the potential to support local food security and increase farmers' income in urban areas.